SURVEY PERILAKU BERBUDI PEKERTI LUHUR ATLET PENCAK SILAT KATEGORI TANDING - Dedi Dasmon Dedi; Qorry Armen Gemael Qorry; Deden Akbar Izzuddin Deden (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
The problem in this research is the noble character behavior of Pencak Silat athletes in the competition category. This study aims to determine how high the Noble Characteristic Behavior of Pencak Silat Athletes in the Competing Category. The research approach uses quantitative research. The method used is a survey with data collection techniques using a questionnaire. The subjects in this study at the Indonesian National Pencak Silat Padepokan (PPNSI) were 63 students. The data analysis technique used quantitative descriptive analysis which was stated in the form of a percentage. The results showed that the noble character behavior of Pencak Silat athletes in the competition category was in the "very poor" category of 9,5% (6 athletes), "not good" by 0% (0 athletes), "quite good" by 15, 9% (10 athletes), "good" at 36.5% (23 athletes), and "very good" at 38.1% (24 athletes). Based on data analysis, the Noble Characteristic Behavior of Pencak Silat Athletes in the Competing Category at the Indonesian National Pencak Silat Padepokan (PPNSI) then the category is good